Protective Effect of Purinergic P2X7 Receptor Inhibition on Acrolein-Induced Urothelial Cell Damage - Taidi, Zhinoos; Mansfield, Kylie J.; Sana-Ur-Rehman, Hafiz; Moore, Kate H.; Liu, Lu (Frontiers in Physiology, 2022)
Patients undergoing chemotherapy with cyclophosphamide experience cystitis due to excretion of a toxic metabolite, acrolein. Cystitis, an inflammation of the bladder, is associated with damage to the integrity of the urothelial barrier. The purinergic P2X7 receptor (P2X7R) is increasingly recognized for its role in inflammation and cell death. P2X7R is expressed abundantly on the bladder urothelium. The aim of this study was to investigate the role of P2X7R in acrolein-induced inflammatory damage in primary cultured porcine bladder urothelial cells. Confluent urothelial cells in culture were treated with acrolein to induce damage; also, with the P2X7R selective antagonist, A804598. Cell viability assay, immunocytochemistry, and trans-epithelial electrical resistance (TEER) studies were carried out to investigate the effect of treatments on urothelial cell function. Acrolein induced a significant reduction in urothelial cell viability, which was protected by the presence of A804598 (10 µM). The urothelial barrier function, indicated by TEER values, was also significantly reduced by acrolein, whereas pre-incubation with P2X7R antagonist significantly protected the urothelial cell barrier from acrolein-induced TEER reduction. The structure of urothelial cell tight junctions was similarly impacted by acrolein treatment, showing the fragmentation of zona occludens-1 (ZO-1) immunoreactivity. Pre-treatment of cells with A804598 countered against the actions of acrolein and maintained ZO-1 expression level and cell structure. The damaging effect of acrolein on urothelial cells integrity could be impaired by inhibition of P2X7R, therefore P2X7R blockade may be a possible therapy in patients with bladder cystitis caused by cyclophosphamide treatment.